Genetics of hearing impairment and peripheral neuropathy in Mali - Yalcouye, Abdoulaye (Department of Pathology, 2023)
Background Hearing impairment (HI), the most common sensory disturbance, affects about 1 in 1000 living newborns globally. Its incidence is reported higher in sub-Saharan African (SSA) populations. HI is caused by environmental and genetics factors. In many developing countries, environmental factors are reported to be the most prevalent aetiologies while genetic causes are predominant in the developed countries. Over 50% of congenital HI has a genetic origin with more than 120 genes identified to date. Despite this large number of known genes, only GJB2 (OMIM: 121011) and GJB6 (OMIM: 604418) are systematically studied in SSA populations for which the prevalence of HI-causal variants is insignificant. Charcot-Marie-Tooth disease (CMT), is the most common inherited peripheral neuropathy (IPN) with a high clinical and genetic heterogeneity and over 100 genes are related to CMT, mostly in populations of Caucasian ancestry. Yet, despite being described more than 130 years ago, there remains a paucity of information on its global prevalence and genetic epidemiology due largely to challenges in diagnosis, especially in countries with limited resources. Over 90% of CMT are caused by mutations in PMP22 (OMIM: 601097), GJB1 (OMIM: 304040), MFN2 (OMIM: 608507), MPZ (OMIM: 159440) genes. HI is the common audiological symptom associated with CMT and is caused by several genes including PMP22 and GJB1. HI and IPN are inherited in autosomal (dominant and recessive), X-linked, and mitochondrial transmission. However, the genetic epidemiology of these diseases are largely unknown in Africa, and have not been investigated in Mali where consanguineous marriage is a common practice that may increase recessive conditions.